Implementation of Students’ Worksheet with Discovery Learning Model Based on the Local Potentials of Mangrove Forest - Djafar, Ismail; Yusuf, Frida Maryati; Baderan, Dewi Wahyuni Kyai (Jurnal Pendidikan MIPA, 2022)
This study aims to reveal the implementation of students’ worksheet that is based on the local potentials of mangrove forest with discovery learning. The subject of this study was students in grade X Science 3 in SMA Negeri 1 Marisa. This is a quantitative research with a pre-experimental design particularly one group pre- and post-test design. The research result revealed that the practicality test for the result of observing students’ activities obtained an average score 87.5% (excellent) for meeting I and 93.8% (excellent) for meeting II. The analysis of learning feasibility was 100% (excellent). The analysis of students’ responses was 96.8% (excellent). The analysis of effectiveness perceived from students’ learning result obtained N-Gain score 61.5 which was categorized medium. It can be concluded that students’ worksheet that is based on the local potentials of mangrove forest with discovery learning can be used for learning to improve students’ learning result on biodiversity material.Keywords: students’ worksheet, mangrove forest, discovery learning. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1252-1261